Biosphere reserves: Attributes for success. (1st March 2017) - Van Cuong, Chu; Dart, Peter; Hockings, Marc
Abstract: Biosphere reserves established under the UNESCO Man and the Biosphere Program aim to harmonise biodiversity conservation and sustainable development. Concerns over the extent to which the reserve network was living up to this ideal led to the development of a new strategy in 1995 (the Seville Strategy) to enhance the operation of the network of reserves. An evaluation of effectiveness of management of the biosphere reserve network was called for as part of this strategy. Expert opinion was assembled through a Delphi Process to identify successful and less successful reserves and investigate common factors influencing success or failure. Ninety biosphere reserves including sixty successful and thirty less successful reserves in 42 countries across all five Man and the Biosphere Program regions were identified. Most successful sites are the post-Seville generation while the majority of unsuccessful sites are pre-Seville that are managed as national parks and have not been amended to conform to the characteristics that are meant to define a biosphere reserve. Stakeholder participation and collaboration, governance, finance and resources, management, and awareness and communication are the most influential factors in the success or failure of the biosphere reserves. For success, the biosphere reserve concept needs to be clearly understood and applied through landscape zoning. Designated reserves then need a management system with inclusive good governance, strong participation and collaboration, adequate finance and human resource allocation and stable and responsible management and implementation. All rather obvious but it is difficult to achieve without commitment to the biosphere reserve concept by the governance authorities. Highlights: We identified 60 successful and 30 less successful biosphere reserves in 42 countries. Most of the successful biosphere reserves belong to the post-Seville generation. Most unsuccessful sites are non-compliant pre-Seville biosphere reserves. Successful sites show evidence of conceptual implementation in design and management. Commitment of the government authority promotes biosphere reserve success.